Military "shadows" in Thailand since the 2006 Coup - Paul Chambers (2018)
In contemporary Thailand, achieving effective civilian control of the armed forces is a daunting challenge. The country's long series of military coups are one outcome of the operational independence generally enjoyed by the military. In most cases, these military interventions have sought to support the political ambitions of the palace and its networks. For almost a decade, Thai politics has been polarized by reactions to the electoral success of former Prime Minister Thaksin Shinawatra and his perceived threat to military and royal power. The military has thus acted as arch-royalist "protector," helping itself to enhance its political status in a monarchy-led parallel state. This paper examines how and why the armed forces continue to remain powerful in Thailand and what prospects exist for diminishing this clout in the messy aftermath of the 2006 coup. © 2013 Copyright Taylor and Francis Group, LLC.